Sócrates según Nietzsche - Greta Rivara Kamaji (Theoría Revista del Colegio de Filosofía, 2003)
The article analyzes Nietzsche’s critique against Socrates specifically in Die Geburt der Tragödie. It explains the way in which Nietzsche considered Socrates as the first symbol of western rationalism, and questions the solidity of Nietzsche’s critique. This task could only be accomplished by the acknowledgement of the elements that led Nietzsche to an image of Socrates that one can estimate as a reductionism. Nonetheless, this does not imply that we should underestimate the fact that Nietzsche’s image of Socrates was not only a negative one: Nietzsche was able, with and through Socrates, to elaborate  one of his most important proposals (i.e., Socrates as a musician), although he did not developed it to its last consequences.